Energy Efficiency, Environment and Health Volume I - González Lezcano, Roberto Alonso; Nocera, Francesco; Caponetto, Rosa Giuseppina (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Cities are widely recognized as environments which can present risks to humans. Risks to health and well-being are measured in three groups of indices: physiological, emotional, and cognitive. The environmental factors discussed in studies include physical factors such as noise, heat load, and air pollution, and social factors include feelings of discomfort, crime, transportation, and access to health services. Some studies even argue that stress and health risks are intrinsic to urban environments and that restoration is intrinsic to green environments. This Topic aims to discuss what spaces can be greened and the effect this has on urban environments. It also discusses the effect of the size and layout of parks, vegetation on the walls and roofs of houses, and the effects of different types of vegetation, building materials, and energy-efficient design. Today's environment demands new design processes, construction techniques, occupancy practices, and management strategies to increase the resilience of the built environment to extreme, uncontrollable, and unpredictable events while providing healthy and sustainable environments for people. This Topic reflects on what the new concept of sustainability for the built environment should be and how to guide new research directions.